2004
DOI: 10.1111/j.1365-263x.2004.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal management of an adolescent with Down's syndrome – a case report

Abstract: A case of periodontitis in a young adolescent Japanese girl with Down's syndrome is presented in this report. The patient received a monthly preventive course of dental care consisting of mechanical plaque control and oral hygiene instruction. After 2.5 years she recovered from progression of periodontal disease both clinically and microbiologically. The importance of clinical care for periodontitis in Down's syndrome patients is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…Therefore oral hygiene becomes poorer with age as seen in this study. Sasaki et al, reported 42% of individuals with Down syndrome with gingivitis in their study [9] . This finding is close to the 49% seen in this study, a significantly higher proportion than in the controls whose oral hygiene improved with age.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore oral hygiene becomes poorer with age as seen in this study. Sasaki et al, reported 42% of individuals with Down syndrome with gingivitis in their study [9] . This finding is close to the 49% seen in this study, a significantly higher proportion than in the controls whose oral hygiene improved with age.…”
Section: Discussionmentioning
confidence: 85%
“…The reasons for the relative failure of a regimen of mechanical supragingival plaque control and scaling and root planning treatment to prevent the exacerbation of the periodontal disease may be more easily understood, against this background of immunological compromise. A recent case report described the treatment of a DS patient by a monthly preventive course of dental care, which included both supragingival and subgingival scaling and root planning, and was successful in preventing the progression of periodontal disease after 2.5‐year period (Sasaki et al . 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Children with DS were significantly less likely to receive dental treatment than their non-DS siblings. Although some authors16 lR have reported that preventive programs have little effect on the progression of periodontal disease in patients with Down syndrome, more recent studies9 24 have shown the effectiveness of frequent preventive care. Yoshihara et al' demonstrated the usefulness of periodic preventive care in suppressing the severity and progression of periodontal disease in subjects with DS.…”
Section: Barriers To Dental Servicesmentioning
confidence: 99%
“…Significant reductions were noted in mean pocket depth (2.5mm and 3.lmm, respectively), mean frequency of periodontal pockets (46% and 91% respectively), and frequency of the prevalence of pathological alveolar bone loss (62% and 100% respectively), when the "managed group" was compared to the "interrupted group." Sasaki et al 24 showed the efficacy of monthly preventive care, which consisted of mechanical plaque control and oral hygiene instruction over a period of two and a half years. Significant reduction in gingival inflammation and probing pocket depths were noted at that time (mean pocket depth at baseline was 2.9mm and after 2.5 years was 1.3mm).…”
Section: Barriers To Dental Servicesmentioning
confidence: 99%